Antioxidant effect of dehydrated rosemary leaves in ripened semi-hard cheese: A study using coupled TG-DSC-FTIR (EGA) - Marinho, Marina Tolentino; Bersot, Luciano dos Santos; Nogueira, Alessandro; Denck Colman, Tiago Andre [UNESP]; Schnitzler, Egon (Elsevier B.V., 2015)
The Evolved Gas Analysis (EGA) is a group of techniques (in this case coupled TG-DSC and FTIR) that can provide information regarding mass changes, exothermal and endothermal events, as well as gaseous products that are evolved during events. In this study, semi-hard cheeses were manufactured and the lipid fractions were assessed by the above-mentioned techniques and others such GC/MS and H-1 NMR, and kinetic parameters were calculated using thermogravimetry. The samples were divided into three portions: (a) cheeses 24 h after manufacture; (b) cheeses after 60 days of ripening; (c) cheeses covered with lard and rosemary after 60 days of ripening. It was observed that the fat from samples treated with rosemary leaves showed higher decomposition temperatures (TG), higher resistance to the oxidation process (T-p = 310.2 degrees C) and enthalpy (1228.5 J g(-1)). The FTIR spectroscopy of the gaseous products of decomposition obtained simultaneously with TG-DSC curves revealed that the main bands could be attributed to -C-H, -COOH stretching with the formation of CO, CO2 and tetradecanoicacid-7-oxomethylester compounds. An increase in the value of the activation energy in cheese covered with rosemary leaves was associated with antioxidant activity. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Thermal analysis; FTIR; Enthalpy; Kinetic study